What’s in a political slogan? (Philology, 2026)
Despite their efficiency and their – practically – mandatory use in political campaigns, slogans are a largely under-researched area of political discourse. This paper focuses on political slogans and investigates them from a cognitive perspective. It aims to provide a description of the conceptual structure underlying political slogans, which could also serve as a stepping stone for further investigations of their ‘witty’, ‘catchy’, and ‘quotable’ character.The paper demonstrates that the conceptual elements in the scenario prototypically employed in political slogans are those of the leader, people being led, a social issue/solution/goal, time, and space. The analysis demonstrates how these scenario elements function prototypically.This hypothesized conceptual structure is tested against a dataset specifically compiled for the present purposes. The dataset includes 25 slogans used within UK and USA political contexts over the last 70 years. The analysis conducted is qualitative.
Keywords: slogans; political discourse; cognitive; scenarios